The role of water treatment abstraction in the flux and greenhouse gas emissions from organic carbon and nitrogen within UK rivers. Issue 10 (22nd October 2016) - Finlay, N. C.; Johnson, K.; Worrall, F.
Abstract: The fate of organic matter through watersheds has been shown to be an important component of the global carbon cycle and processes in rivers can rapidly transfer carbon from the terrestrial biosphere to the atmosphere. However, the role of water abstraction in diverting organic matter from freshwater has not been considered. This study used two methods to estimate the amount of organic carbon removed by water treatment processes, first, by estimating the amount of carbon that has to be removed given the abstracted volumes and the freshwater composition; and, second, estimated from reports of the production and composition of water treatment residuals from water companies. For the UK, the median total organic carbon removed by water abstraction was 46 ktonnes C/yr, this equates to a median per capita value of 0.76 kg C/ca/yr. The median total organic nitrogen removed was 4.0 ktonnes N/yr, equivalent to 0.07 kg N/ca/yr. The removal of TOC by water abstraction represents 1.5% of the total removal rate across UK watersheds. The release of greenhouse gases from UK rivers is now estimated to be between 12, 754 and 32, 332 ktonnes CO2eq /yr equivalent to between 55 and 127 tonnes CO2eq /km 2 /yr with fluvial organic matter between 8800 and 15, 116 ktonnes CO2eq /yr in the proportion 6:86:8 N2 O:CO2 :CH4 . The emissions factor for 1 tonne of organic carbon entering the UK fluvial network has a median value of 2.95 tonnes CO2eq /yr with a 5th to 95th percentile range of 2.55 to 3.59 tonnes CO2eq /yr. Globally, a per capita values for countries with municipal treated water supply would be 0.8 to 0.86 kg C/ca/yr. Key Points: The removal of TOC by water abstraction represents 1.5% of the total removal rate across UK watersheds The emissions factor for 1 tonne of organic carbon entering the UK fluvial network has a median value of 3.01 tonnes CO2eq/yr Globally, a per capita values for countries with municipal treated water supply would be 0.8–0.86 kg C/ca/yr